Narsistik Era Digital: Investigasi mendalam harga diri dan intensitas penggunaan media sosial - Darmawan, Kevin; Pratikto, Herlan; Suhadianto, Suhadianto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
The rapid development of social media can affect student development, one of which is Instagram which ranks at the top as the social media platform that shows the most narcissistic side. This study aims to determine the relationship between self-esteem and intensity of Instagram social media use with narcissistic tendencies in college students. The population in the study was 941 students. Participants in the study were 281 students using accidental sampling techniques. The instruments in the study used the Guttman scale and Likert scale. The method used for data analysis is multiple regression with the help of SPSS 25.0 for windows. The results showed that there was a positive relationship between self-esteem and intensity of Instagram social media use with narcissistic tendencies in college students. The advice conveyed is able to control feelings when getting praise from other individuals when uploading activities on Instagram and reduce the intensity of Instagram use so as not to become a very intense user (classified as high) which can lead to narcissistic tendencies. Perkembangan media sosial yang berkembang pesat mampu mempengaruhi perkembangan mahasiswa, salah satunya adalah Instagram yang menempati urutan teratas sebagai platfrom media sosial paling banyak menunjukkan sisi narsistik. Penelitian ini bertujuan untuk mengetahui hubungan antara harga diri dan intensitas penggunaan media sosial instagram dengan kecenderungan narsistik pada mahasiswa. Populasi pada penelitian adalah 941 mahasiswa. Partisipan pada penelitian adalah 281 mahasiswa dengan menggunakan teknik accidental sampling. Instrumen pada penelitian menggunakan skala guttman dan skala likert. Metode yang digunakan untuk analisis data adalah regresi berganda dengan bantuan SPSS 25.0 for windows. Hasil penelitian menunjukkan bahwa terdapat hubungan positif antara harga diri dan intensitas penggunaan media sosial instagram dengan kecenderungan narsistik pada mahasiswa. Saran yang disampaikan mampu mengendalikan perasaan ketika mendapatkan pujian dari individu lain saat mengunggah aktivitas di instagram dan mengurangi intensitas penggunaan Instagram agar tidak menjadi pengguna yang sangat intens (tergolong tinggi) yang dapat memunculkan kecenderungan narsistik.